Flexibility for performance. For professionals - Magill, Lenny; Durkin, Todd.; Eveland, Brian; Time Zone Multimedia (San Diego, CA : Time Zone Multimedia, 2006)
Learn over 30 stretches for the entire body.
At head of title on container: TD Performance presents.
Trainer, Todd Durkin.
DVD.
Keywords: Stretching exercises; Physical education and training; Physical fitness; Athletes -- Physical fitness; Athletes -- Health; Sports -- Physical fitness